Receiver Operator Characteristics (ROC) Analyses of Complete Blood Count (CBC) Delta - S Balamurugan; V Rohith (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Delta check is a quality control tool that involves comparison of lab test result of current sample with that of previous sample from the same patient based on specified criteria. Though chemical analytes have been studied extensively for delta checking, literature is limited for haematology tests. Aim: In this ‘simulation’ study, we aimed to evaluate the performance characteristics of Complete Blood Count (CBC) tests in delta checking of specimen mix-ups/mis-identification using Receiver Operator Characteristics (ROC) analyses. Materials and Methods: Retrospective data from hospital patients (aged >18 years) for whom CBC tests were done within 14 days of primary testing were collected. Two groups were created: actual delta and simulated pseudo delta, the latter group simulating the real-time misidentified or mislabeled specimens. Performance characteristics of CBC analytes in detecting specimen mix-ups were evaluated by ROC curves and Areas Under Curves (AUC) using MedCalc statistical software. Results: AUC values observed for CBC analytes were: MCV (0.90), MCH (0.87) and RDW (0.82), Haematocrit (0.76), Haemoglobin (0.75), RBC count (0.75), Platelet count (0.72), MCHC (0.61) and Total leucocyte count (0.64). Indices of individuality (II) for CBC analytes were: MCH (0.27) <MCV (0.29) <Haemoglobin (0.42) <Haematocrit (0.42) <Platelet count (0.42) <RBC count (0.51) <Total WBC count (0.54) <RDW (0.61) <MCHC (0.88). Conclusion: MCV and MCH are the most ideal CBC analytes for delta checking of specimen mix-ups/mis-identification as they have low indices of individuality/Reference change values (RCV) and high AUC values. Integration of delta check in the Lab Information System (LIS) is an effective quality practice that can monitor release of erroneous lab results.